2014
DOI: 10.1136/bmj.g1622
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine patches in pregnant smokers: randomised, placebo controlled, multicentre trial of efficacy

Abstract: Objective To determine the efficacy of 16 hour nicotine patches among pregnant smokers, with the dose individually adjusted according to saliva cotinine levels (potential range 10-30 mg/day).Design Randomised, double blind, placebo controlled, parallel group, multicentre trial (Study of Nicotine Patch in Pregnancy, SNIPP) between October 2007 and January 2013. Setting 23 maternity wards in France.Participants 476 pregnant smokers aged more than 18 years and between 12 and 20 weeks' gestation, who smoked at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 46 publications
1
100
1
2
Order By: Relevance
“…A similar reduction in the risk of CAs among women prescribed NRT was found in a more recent trial including 476 pregnant smokers from 23 maternity wards in France. 14 We found that the odds of MCAs in the NRT group were 7% higher compared with smokers, although this finding was not statistically significant. Similarly, the absolute risks of system-specific anomalies were also generally higher than in the overall population and in smokers, although these differences were small.…”
Section: Interpretation In Light Of Current Literaturecontrasting
confidence: 44%
See 1 more Smart Citation
“…A similar reduction in the risk of CAs among women prescribed NRT was found in a more recent trial including 476 pregnant smokers from 23 maternity wards in France. 14 We found that the odds of MCAs in the NRT group were 7% higher compared with smokers, although this finding was not statistically significant. Similarly, the absolute risks of system-specific anomalies were also generally higher than in the overall population and in smokers, although these differences were small.…”
Section: Interpretation In Light Of Current Literaturecontrasting
confidence: 44%
“…10 Evidence of safety specifically in relation to CA risks is limited to 1 observational study of linked clinical data from Denmark, which did not find an increased risk with major CAs, and 2 randomized controlled trials of pregnant women in England and France, both of which found a reduced risk but were not adequately powered to assess this outcome. [12][13][14] Using a large population-based pregnancy cohort, the present study investigated whether exposure to NRT increases the risk of major congenital anomalies (MCAs) compared with pregnant women who neither smoked nor were prescribed NRT antenatally and who smoked during pregnancy.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Owing to the risk of compensatory smoking, health gains are only realised if cutting down is accompanied with NRT. Preliminary studies involving pregnant smokers suggest that using NRT while cutting down is safe (Berlin et al 2014), although pre-cessation use has not been addressed in formal guidelines (Zwar et al 2014).…”
Section: Dangers Of Quitting and Treatmentmentioning
confidence: 99%
“…The proportion of deaths attributable to smoking was approximately 24 % for men and 6 % for women. From the total premature deaths, nearly one in four (for those aged between 30-44 years) also one in three (for those aged between 45-59 years) were attributed to tobacco use [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to reduce the number of diseases caused by smoking also implicitly the costs entailed by these diseases, requires a reduction in smoking prevalence. Increasing the rate smoking cessation is considered the only high-impact strategy that can lead to short-term improvement [3,4].…”
Section: Introductionmentioning
confidence: 99%